A facticidade da vida nas origens cristãs: uma leitura das interpretações heideggerianas de Paulo a Agostinho - Dias Júnior, João de Paula (2023)
This paper attempts at analyzing the Christian origins of facticity in the philosophical development of the young Heidegger, based on the first two lectures from GA 60, namely, the Introduction to the Phenomenology of Religion, from Winter Semester at Freiburg, in 1920-21, and Augustine and Neo-platonism, from Summer Semester, 1921, analyzing the early Christianity, more specifically, the Pauline situation to get to the Augustinian reflection about the trouble (molestia) and temptations as a constitutive way of factical life. Thus, this paper has the purpose of making a reflection about Heidegger’s phenomenological reading of some Pauline epistles and the Book X of Confessions, by Augustine, trying to recognize in Christianity a concrete example of the experience of facticity. To do so, first a general overview of what is the factical life and how Heidegger develops it in his first writings will be done, in order to bring a genealogy project of facticity and build a structural basis of concepts, so that it is possible to take the second step, which is analyzing the experience of factual life in the early Christianity looking for a clarification about the structures of the Christian facticity to, then, understand the factual experience situation of Paul, the Apostle. Martin Heidegger understands that the Apostle was able to clearly develop in his writings the original Christian experience, that is not objectively closed, but is given existentially in facticity. In the follow up, the next chapter purposes a glance at Heidegger’s phenomenological reading about Book X of Confessions by Augustine of Hippo. At this point, it is noted how the curare and the tentatio are given as a fundamental character of factical life, bringing the trouble (molestia) as the weight of life in front of existence and the temptations as a way of living the humanity authentically.